Water Circulation Monitoring System in The Vanname Shrimp Cultivation based on Internet of Thing - Intan, Indo; Nurlina, nfn; Pangerang, Fitriaty (Jurnal Pekommas, 2020)
The cultivation of vaname shrimp is a leading commodity because of several advantages. Some shrimp farmers still practice traditional cultivation which is less effective and efficient in terms of labor and costs. This research was conducted as a solution based on current technology to overcome this problem. The goal is as an alternative to combine microcontroller technology and the IoT so that real-time and objective information is produced when monitoring water circulation in the prototype of vannamei shrimp culture is carried out. The design method of water circulation monitoring hardware and software is adjusted to the needs of the input devices for the three sensors (temperature, pH, and salinity). Microcontroller data processing is sent via synchronization between the wireless sensor network and the web. The results obtained show that the speed of data transmission is in accordance with real-time conditions and is not significantly affected by distance problems, because IoT has brought distant ones closer. Monitoring information also shows the circulation process when the water quality changes from normal conditions. This monitoring can be developed on a broader scale so that it can be an alternative technology with direct benefits for vannamei shrimp farmers.